Effects of red light on sleep quality in cardiac intensive care unit patients: A randomized controlled trial - Seyed Mahdi Motahary; Amir Mohammad Barati; Neda Mirbagher Ajorpaz (Nursing Practice Today, 2025)
Background & Aim: Sleep disturbances are prevalent in cardiac intensive care units. Due to the side effects of sleep medications, this study aimed to assess the impact of red light on the sleep quality of patients in cardiac intensive care units. Methods & Materials: In a randomized clinical trial, 80 patients in both study groups were admitted to the coronary care unit of Shahid Beheshti Hospital in Kashan, Iran. In the intervention group, red light replaced the white light in the room for two consecutive nights. The sleep quality, insomnia severity, and frequency of insomnia causes of the patients in both groups were assessed before the intervention and on the first and second days after the intervention using the St. Mary's Hospital Sleep Quality Questionnaire. Results: The sleep quality score of patients in the intervention group was higher after the intervention than in the control group (p=0.001). A statistically significant difference was observed between the two groups in the first and second days after that for sleep quality score, frequency of insomnia, and insomnia severity (P= 0.001). Comparing the scores of the dimensions of the Sleep Quality Questionnaire before and after the intervention in the two groups showed that the two groups did not have a statistically significant difference in these dimensions (p>0.017). Conclusion: Red light led to an improvement in sleep quality scores and a reduction in the severity and frequency of insomnia in patients admitted to the cardiac intensive care units. Its simplicity and low cost make it a recommended approach for improving their sleep.